Photoresponse and electrical properties of Al/nanostructure NiFe2O4/p-Si/Al photodiode - Cavas, M.; Alahmed, Z. A.; Albrithen, H. A.; Yakuphanoğlu, Fahrettin (Springer, 2014)
The electrical characterization of Al/NiFe2O4/p-Si/Al photodiode was investigated by current-voltage and capacitance-voltage characteristics. The barrier height and ideality factor magnitudes of the Al/NiFe2O4/p-Si/Al diode were found to be 0.82 and 5.2 eV, respectively. The optical properties of the NiFe2O4 film have been investigated and the optical band gap was found to be 2.66 eV. The photoresponse results indicate that the diode exhibits a photodiode behavior, and the photocurrent of the diode increases by increasing illumination intensity. The density of interface states of the diode was determined by conductance method. The obtained results show that the series resistance of the diode is decreased with increasing frequency. The obtained results indicate that NiFe2O4 spine oxide material can be used in diode applications.
Keywords: Photo diode; Schottky diode; Nanomaterial; Sol gel method